IMPLEMENTASI PERATURAN DAERAH NOMOR 10 TAHUN 2005 TENTANG PAJAK HOTEL DI KABUPATEN MELAWI - Rikka Septiandini E.42009057 (FISIP Universitas Tanjungpura Pontianak, 2021)
This research is intended to generate recommendations on optimizing the implementation of hotel taxes in the District of Nanga Pinoh Melawi. The title of this study was chosen as based the realization revenue of hotel taxes is still not achive the specific target. This research uses Qualitative Research Methods. Because it describes the certain situation, attitude, behaviour, view, phenomenon, and the process which occurs in location of research. This study uses two phases: The first phase to find problems policy, and the second to see its implementation in the field, formulate and provide recommendations. The location of research is take place in Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah (DPPKAD) Melawi Regency. The conclusion of this study is the level of awareness and discipline in tax payments from taxpayers who still low, although a small portion of taxpayers are aware of their obligations. The taxpayer have to pay hotel taxes but in providing data about this hotel taxes are still not transparent. The recommendations that were provided for the implementation of hotel taxes in the District of Nanga Pinoh Melawi Regency is focused on how to optimize the hotel tax revenue to effectively disseminate sustainable, do the persuasive approach and provide an understanding of the importance paying taxes and the benefits of local tax payments to the taxpayer in order to raise the full support. Keywords: Public Policy, Hotel Taxes, Optimization.